The Influence Of Performance Appraisal Satisfaction On Nurses’ Motivation And Their Work Outcomes In Critical Care And Toxicology Units - Nagah Abd El-Fattah Mohamed Aly; Safaa Moustafa El-Shanawany (European Scientific Journal, ESJ, 2016)
Nurses’ satisfaction with performance appraisal is a critical and important aspect for increasing intrinsic motivation and achieving better work outcomes among nurses. The present study attempted to understand how satisfaction with the performance appraisal process among nurses affects their motivation and their work outcomes as well as to identify the influence of nurses’ motivation on nurses’ work outcomes. Additionally, it tried to describe obstacles that hinder nurses’ satisfaction with performance appraisal process. The study applied cross-sectional descriptive correlation study amongst 323 nurses in Critical Care and Toxicology Units. This study revealed that nurses were dissatisfied with the performance appraisal process and less motivated in their work. Also, their performance and productivity were at fair levels. The present study found that nurses’ satisfaction with performance appraisal had a highly significant positive impact on nurses’ intrinsic motivation and nurses’ work outcomes. This study also indicated that nurses’ intrinsic motivation had a highly significant positive relationship with nurses’ work outcomes. Additionally, nurses perceived that managerial and organizational forces may hinder their satisfaction with the performance appraisal process.